Nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material and preparation method thereof

By forming a nano/micro-honeycomb sandwich structure in Ca3Co4O9 ceramics, using atmospheric or double-sided-vacuum melt-implantation technology, the problem of insufficient thermoelectric performance of existing Ca3Co4O9 ceramics is solved, and higher thermoelectric performance and wider application fields are achieved.

CN119899956AActive Publication Date: 2025-04-29XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510069837.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The thermoelectric properties of existing Ca3Co4O9 ceramics are difficult to meet the strict requirements of thermal energy dissipation technology of hypersonic vehicles.

Method used

The preparation method of nano/micro-honeycomb sandwich structure is adopted, and the enhanced metal penetrates into the porous Ca3Co4O9 ceramic matrix through normal pressure or double-sided-vacuum melt-implantation technology to form a honeycomb sandwich structure.

Benefits of technology

Improves the thermoelectric properties of the material, including conductivity, Seebeck coefficient and power factor, and is suitable for thermal management and waste heat recovery in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899956A_ABST
    Figure CN119899956A_ABST
Patent Text Reader

Abstract

The invention discloses a Ca3Co4O9-based metal ceramic material with a nano / micro honeycomb sandwich structure and a preparation method of the Ca3Co4O9-based metal ceramic material, and belongs to the technical field of high-temperature ceramic-based thermoelectric conversion materials.The preparation method comprises the steps that a heated and molten alloy is infiltrated into a surface-modified porous Ca3Co4O9 ceramic matrix through a normal-pressure infiltration or double-face-vacuum melting infiltration technology, and the Ca3Co4O9-based metal ceramic material with the nano / micro honeycomb sandwich structure is obtained; and the Ca3Co4O9 metal ceramic material is successfully prepared. According to the method, after the surface of ceramic is modified, a Ca3Co4O9 ceramic matrix is vertically placed on an alloy under the normal pressure or vacuum condition, after the alloy is heated and melted, an alloy liquid phase spontaneously fills pores in the ceramic or permeates into the ceramic due to the action of capillary force, and after the alloy is solidified, a two-phase combined honeycomb sandwich structure is formed. The conductivity and seebeck coefficient of the material can be effectively improved, so that the ZT value of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-temperature ceramic-based thermoelectric conversion materials, and specifically relates to a nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 Metal-ceramic material and preparation method thereof. Background Art

[0002] For hypersonic vehicles, heat treatment during acceleration and breaking through the atmosphere has always been one of the key issues in its development. At present, the conduction and dissipation of heat energy is the main form of aerodynamic heat dissipation, that is, transferring heat from high-temperature areas to low-temperature areas, and finally dissipating it through radiation, thereby ensuring the safety of the internal structure, equipment and fuel of the aircraft. This technology is called heat dissipation technology, which can be divided into heat-resistant structures and multifunctional structures according to the diversity of structural functions. Multifunctional structures refer to structures that can achieve multiple functions such as load-bearing, heat insulation and heat protection. Currently, common multifunctional structures include load-bearing / heat-protection integrated structures and composite structures that meet other functions.

[0003] Oxide thermoelectric materials show excellent stability at high temperatures, simple preparation process, low cost, non-toxicity, and little environmental pollution, so they have good development prospects in the field of hypersonic aircraft. 3 Co 4 O 9 It is a thermoelectric material that has attracted much attention. It has a large thermoelectric potential and low resistivity, and has the advantages of anti-oxidation, high temperature resistance, low cost and long service life. 3 Co 4 O 9 Ceramics have better thermal stability at high temperatures and are suitable for use in harsh environments. 3 Co 4 O 9 The material performs well in many aspects, but its current thermoelectric performance is still difficult to meet the stringent requirements of hypersonic vehicles for heat dissipation technology. At this stage, the thermoelectric performance of this material is difficult to meet the requirements. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 Based on metal ceramic material and preparation method thereof, to solve the problem of Ca 3 Co 4 O 9 The problem that ceramic performance does not meet the requirements of practical applications.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 The preparation method of the base metal ceramic material comprises the following steps: Step 1: Modifier solution is used to treat porous Ca 3 Co 4 O 9 Ceramic modification to obtain modified porous Ca 3 Co 4 O 9 Ceramic, the Ca 3 Co 4 O 9 The pores in the ceramic matrix are radial holes; Step 2: Modified Ca 3 Co 4 O 9 The ceramic substrate is polished and ground to obtain the polished porous Ca 3 Co 4 O 9 ceramics; Step 3: Infiltrate the reinforced metal into the polished Ca2O3 by a normal pressure melt infiltration method or a double-sided vacuum melt infiltration method. 3 Co 4 O 9 In the ceramic matrix, a nano / micro honeycomb sandwich structure Ca is obtained 3 Co 4 O 9 Based on metal ceramic material, the nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 The base metal ceramic material includes a base material and a reinforcement phase, wherein the base material is Ca 3 Co 4 O 9 Ceramics, the reinforcing phase is filled with Ca 3 Co 4 O 9 In the ceramic pores or attached to Ca 3 Co 4 O 9 In the side wall of the ceramic pore; The process of the atmospheric pressure infiltration method is to grind the Ca 3 Co 4 O 9 The ceramic and the reinforcing metal are placed together in a heating furnace, Ca 3 Co 4 O 9 The lower end of the ceramic is in contact with the upper end of the reinforcing metal, and the Ca3 Co 4 O 9 The pores of the ceramic are radially perpendicular to the reinforcing metal. The heating furnace is heated and insulated after being washed with protective gas to obtain a nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 Base metal ceramic materials; The process of the double-sided vacuum melting method is to grind the porous Ca 3 Co 4 O 9 The ceramic and the reinforcing metal are placed together in a vacuum heating furnace, Ca 3 Co 4 O 9 The lower end of the ceramic substrate is in contact with the upper end of the reinforcing metal. 3 Co 4 O 9 The pores of the ceramic are radially perpendicular to the reinforcing metal. The vacuum heating furnace is heated and kept warm after washing, and then the Ca is turned over. 3 Co 4 O 9 Ceramics, repeated washing, heating and insulation, to obtain nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 Base metal ceramic materials.

[0006] A further improvement of the present invention is: Preferably, in step 1, the modifier is any one of TEOA, SDBS, DA, KH-550 or NaOH.

[0007] Preferably, in step 1, the porous Ca 3 Co 4 O 9 The process of ceramic modification is to convert Ca 3 Co 4 O 9 The ceramic substrate is immersed in the modifier solution, and after the container is sealed, it is immersed and modified for 24 hours.

[0008] Preferably, in step 2, the polishing is to polish the porous Ca by sandpaper of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh in sequence. 3 Co 4 O 9 Ceramic polishing.

[0009] Preferably, in step 3, the reinforcing metal is Ag-Cu alloy, Ag or Al-Cu alloy.

[0010] Preferably, in step 3, the process of gas washing by the atmospheric pressure infiltration method is: introducing argon gas into the furnace chamber at a flow rate of 30-80 mL / min until the air in the furnace is exhausted.

[0011] Preferably, in step 3, the heating temperature of the atmospheric pressure infiltration method is 1123-1273 K, and the holding time is 0.5-2 h.

[0012] Preferably, in step 3, the gas washing process in the double-sided vacuum melt infiltration method is: evacuate the air in the vacuum heating furnace to reduce the pressure in the vacuum heating furnace to below 30 Pa; then, introduce argon gas into the vacuum heating furnace until the pressure in the vacuum heating furnace increases to 0.5 Mpa; finally, maintain the pressure for 10-60 min and then evacuate the gas in the vacuum heating furnace again, and repeat the above steps 2 to 3 times.

[0013] Preferably, the heating process of the double-sided vacuum melt infiltration method is: introducing argon gas into the vacuum heating furnace to atmospheric pressure, heating the heating furnace to 1123-1273 K, extracting argon gas to a pressure of less than 30 Pa in the vacuum heating furnace, and keeping the temperature for 0.5-2 h.

[0014] A nano / micro honeycomb sandwich structure Ca prepared by any one of the preparation methods described above 3 Co 4 O 9 The base metal ceramic material comprises a base material and a reinforcement phase, wherein the base material is a porous Ca 3 Co 4 O 9 Ceramic, the Ca 3 Co 4 O 9 The pores in the ceramic matrix are radial pores, the reinforcing phase is metal, and the reinforcing phase is filled in Ca 3 Co 4 O 9 In the ceramic pores or attached to Ca 3 Co 4 O 9 In the side wall of the ceramic pore.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention relates to the technical field of high-temperature ceramic-based thermoelectric conversion materials and proposes a method for preparing a honeycomb sandwich structure Ca 3 Co 4 O 9 A new method for metal ceramic materials. The heated molten alloy is infiltrated into the porous Ca by atmospheric pressure impregnation or double-sided vacuum melt infiltration technology. 3 Co 4 O 9In the ceramic matrix, Ca 3 Co 4 O 9 Metal ceramic materials. This method uses atmospheric pressure impregnation or vacuum conditions to impregnate Ca 3 Co 4 O 9 The ceramic matrix is ​​placed vertically on the alloy. After the alloy is heated and melted, the alloy liquid phase spontaneously fills the internal pores of the ceramic or penetrates into the interior of the ceramic due to the action of capillary force. After the alloy solidifies, a honeycomb sandwich structure combining the two is formed. Generally speaking, alloys bring high electrical conductivity while also improving the thermal conductivity of metal ceramics. However, this structure introduces a large number of metal / non-metal interfaces, which are mainly connected by covalent bonds or hydrogen bonds and van der Waals forces. The existence of such interfaces can reduce the phonon transmission channel and effectively scatter phonons, thereby reducing thermal conductivity. The existence of the interface also inhibits the transport of carriers, effectively improving the Seebeck coefficient of the material without reducing electrical conductivity. The preparation method has simple steps and low raw material cost. The alloy is infiltrated into the porous Ca 3 Co 4 O 9 In the internal pores of the ceramic body, a Ca with a honeycomb sandwich structure is prepared. 3 Co 4 O 9 Metal-ceramic materials can optimize the mechanical and thermoelectric properties of ceramic materials, thereby broadening the application of Ca 3 Co 4 O 9 The application field of thermoelectric materials based on this method can effectively prepare Ca 3 Co 4 O 9 The metal-ceramic thermoelectric material has good material stability and excellent mechanical properties, which enables the material to serve for a long time at high temperatures. It is suitable for waste heat recovery in high-temperature fields such as thermal management of hypersonic aircraft, and has broad application prospects.

[0016] Furthermore, when the holding temperature is within the range of 1073-1273 K, the porosity of the prepared ceramic matrix composite material decreases by more than 60% to only about 3%, showing an ideal infiltration effect. The material has excellent thermoelectric properties, with a maximum electrical conductivity of 38.48 S / m, a power factor of 0.30 mW / (m·K²), and a thermoelectric figure of merit of 0.24.

[0017] The present invention also discloses a nano / micro honeycomb sandwich structure Ca prepared by the above preparation method. 3 Co 4 O 9Based on thermoelectric materials, this ceramic material has developed a multifunctional structure that integrates load-bearing, heat protection and power supply. A layer of thermoelectric ceramic-based composite material is added to the high-temperature resistant layer on the surface of the aircraft, which can generate electricity by utilizing the huge temperature difference between the inside and outside, and realize the recycling of waste heat. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Ag-Cu alloy / Ca 3 Co 4 O 9 SEM images of metal-ceramic materials parallel to the infiltration direction; Figure 2 Ag-Cu alloy / Ca 3 Co 4 O 9 SEM images of metal-ceramic materials perpendicular to the infiltration direction; Figure 3 Ag-Cu alloy / Ca 3 Co 4 O 9 SEM-EDS line scan data at the boundary between two phases of metal-ceramic materials; Figure 4 Ag-Cu alloy / Ca 3 Co 4 O 9 XRD patterns of metal ceramic materials; Figure 5 Ag-Cu alloy / Ca 3 Co 4 O 9 Interfacial contact resistance of metal-ceramic materials; Figure 6 Ag-Cu alloy / Ca 3 Co 4 O 9 Infrared thermal imaging of metal ceramic materials heated at 1073K; Figure 7 The Ag-Cu alloy / Ca of Example 1 and Example 2 3 Co 4 O 9 Overall thermal conductivity of cermet materials; Figure 8 The Ag-Cu alloy / Ca of Example 1 and Example 2 3 Co 4 O 9 Seebeck coefficient of metal-ceramic materials; Fig. 9 The Ag-Cu alloy / Ca of Example 1 and Example 2 3 Co 4 O9 Electrical conductivity of cermet materials; Fig.10 The Ag-Cu alloy / Ca of Example 1 and Example 2 3 Co 4 O 9 Power factor of metal-ceramic materials; Fig.11 The Ag-Cu alloy / Ca of Example 1 and Example 2 3 Co 4 O 9 ZT figure of merit of metal-ceramic materials. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0020] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0021] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0022] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0023] In this experiment, porous Ca 3 Co 4 O 9The porous ceramic, the preparation method and the specific materials can be found in the patent document with the publication number of CN 115710137 A. The pure triethanolamine (TEOA, C 6 H 15 NO 3 , Sinopharm Group), sodium dodecylbenzenesulfonate (SDBS, C 18 H 29 NaO 3 S, Sinopharm Group), dopamine (DA, C 8 H 11 NO 2 , Sinopharm Group), silane coupling agent (KH-550, C 9 H 23 NO 3 Si, Sinopharm Group) and sodium hydroxide (NaOH, Sinopharm Group) are used as modifiers, and metals such as Ag-Cu alloys (AgCu3, AgCu7.5, AgCul0, AgCu28 and AgCu55, etc.), Ag and Al-Cu alloys (ZAICu4, ZAICu10 and ZAICu33, etc.) are used as reinforcement phases. The reinforcement metals have excellent conductive properties.

[0024] The invention discloses a nano / micro honeycomb sandwich structure Ca 3 Co 4 O 9 A method for preparing a metal-ceramic material, the method comprising the following steps: Step 1: Pretreatment of ceramic matrix and reinforcement phase.

[0025] Step 1.1 Prepare the modifier solution. The modifier is TEOA, SDBS, DA, KH-550 or NaOH, and the concentration of the modifier solution is 0.05-1 mol / L. Take the preparation of 100 ml, 1 mol / L NaOH as an example, calculate that the required drug is 0.4 g of NaOH powder, weigh it and pour it into a beaker, add distilled water and stir with a glass rod to dissolve, add the liquid level to the 100 ml scale, prepare the required solution, and label it for use. In this process, the groups carried by the modifier are introduced to increase the subsequent Ca 3 Co 4 O 9 The wettability of ceramics and molten metals. Specifically, DA, TEOA and NaOH are used to provide -OH; SDBS is a sulfonic acid group (-SO 3 H); KH-550 provides amino groups to increase the polarity of the material surface and to increase the wettability with metal solutions.

[0026] Step 1.2: Porous Ca 3 Co 4 O9 The ceramic wire is cut into small cubes of 2×2×3 cm and placed in a beaker. The solution prepared in 1.1 is drained into the beaker with a glass cup until the Ca 3 Co 4 O 9 The ceramic was immersed, sealed with plastic wrap and immersed for 24 hours. 3 Co 4 O 9 Take out the ceramics and put them in an insulated box to dry for later use.

[0027] Step 1.3: The roughness of the ceramic surface and the oxide layer of the alloy have a great influence on the infiltration effect. Therefore, it is necessary to test the modified Ca 3 Co 4 O 9 The ceramic matrix and alloy were pretreated accordingly. The Ca alloy was sanded in sequence using sandpapers of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh. 3 Co 4 O 9 The ceramic substrate is polished until the surface is smooth, and the polished sample is polished with a polishing machine for 10-20 minutes to ensure that there are no obvious scratches on the surface. After polishing, it is placed in a beaker filled with alcohol and ultrasonically washed 2-3 times, and then dried for use. The alloy is polished with sandpaper before the experiment, and then polished to remove the oxide layer on the surface before use. Through the polishing process, it can ensure that the infiltration effect is consistent in all parts, so that the metal distribution in the prepared metal ceramic is as uniform as possible.

[0028] Step 2, Ag-Cu alloy / Ca 3 Co 4 O 9 Atmospheric pressure infiltration process of metal ceramics.

[0029] Step 2.1, put the polished AgCu28 alloy raw material into the crucible as the reinforcing metal, and add the modified Ca 3 Co 4 O 9 The ceramic matrix is ​​fixed on top of the reinforcing metal, Ca 3 Co 4 O 9 The pore direction of the ceramic matrix is ​​perpendicular to the direction of the reinforcing metal, Ca 3 Co 4 O 9 The lower end of the ceramic substrate is in contact with the alloy and is fed into the quartz tube, and the tube furnace is closed; Step 2.2, purge the tube furnace: first connect the pipeline; then, introduce argon into the furnace chamber at a flow rate of 30-80 ml / min for 5-10 min until the air in the furnace is basically exhausted; Step 2.3, after purging, heat the tube furnace to 1123-1223 K at a heating rate of 2-8 K / min; then keep the temperature for 0.5-2 h; finally, cool the tube furnace naturally to room temperature to obtain Ca 3 Co 4 O 9 Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm for testing the pore structure and thermoelectric properties.

[0030] Step 3, Ag-Cu alloy / Ca 3 Co 4 O 9 Research on double-sided vacuum melt infiltration process technology of metal ceramics.

[0031] Step 3.1, put the polished AgCu28 alloy raw material into the crucible as the reinforcing metal, and add the modified Ca 3 Co 4 O 9 The ceramic matrix is ​​fixed on the reinforcing metal, Ca 3 Co 4 O 9 The pore direction of the ceramic substrate is perpendicular to the direction of the reinforcing metal, the lower end is in contact with the alloy, and then the furnace cover of the vacuum heating furnace is closed; Step 3.2, purge the vacuum heating furnace: first, evacuate the air in the vacuum heating furnace to reduce the pressure in the vacuum heating furnace to below 30 Pa; then, introduce argon gas into the vacuum heating furnace until the pressure in the vacuum heating furnace reaches about 0.5 MPa; finally, maintain the pressure for 10-60 minutes and then evacuate the gas in the vacuum heating furnace again, and repeat the above steps 2-3 times; Step 3.3, after purging, argon gas is introduced into the vacuum heating furnace to atmospheric pressure, and the vacuum heating furnace is heated to 1123-1223 K at a heating rate of 2-8 K / min; then, the argon gas in the vacuum heating furnace is extracted until the pressure in the vacuum heating furnace is less than 30 Pa, and the temperature is kept for 0.5-2 h; finally, the vacuum heating furnace is naturally cooled to room temperature to obtain Ca 3 Co 4 O 9 Cermets. This process removes air from the furnace and prevents oxidation of the metal.

[0032] Step 3.4, fix the opposite side of the infiltrated surface of the metal ceramic infiltrated in step 3.3 above the alloy. Then close the cover of the vacuum heating furnace; repeat steps 3.2 and 3.3 to obtain Ca 3 Co 4 O 9Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm for testing the pore structure and thermoelectric properties.

[0033] It should be noted that the above steps 2 and 3 are parallel steps. In the above preparation process, after the reinforcing metal melts, under the action of capillary force, the liquid phase spontaneously fills the internal pores of the ceramic or penetrates into the interior of the ceramic. After the alloy solidifies, a two-combined composite material is formed. The reinforcing metal phase is in the ceramic, forming a honeycomb sandwich structure, and the reinforcing metal phase is also infiltrated into the ceramic.

[0034] The second aspect of the present invention discloses a nano / micro honeycomb sandwich structure Ca prepared by the above preparation method. 3 Co 4 O 9 The base metal ceramic material comprises a base material and a reinforcement phase; the base material is a porous Ca 3 Co 4 O 9 ceramic, the pore size is about 2.5 μm, the reinforcing phase is a reinforcing metal, and the reinforcing phase is filled in Ca 3 Co 4 O 9 In the ceramic pores or attached to Ca 3 Co 4 O 9 In the side wall of the ceramic pore.

[0035] Step 4: Ca 3 Co 4 O 9 Study on components of metal ceramic preparation.

[0036] In steps 2.1 and 3.1, the alloy type can be replaced with Ag-Cu alloy, Al-Cu alloy or other suitable metal materials of other specifications, and the melting temperature in steps 2.3 and 3.3 can be replaced with a temperature suitable for the alloy.

[0037] The main process of double-sided vacuum melt infiltration technology includes several key steps: first, the reinforcement powder is made into a porous preform by freeze drying and other methods; then, the metal is placed at the bottom of the porous preform and heated under vacuum conditions, so that the metal melts and spontaneously penetrates into the gaps of the preform through the capillary force generated by the porous structure itself. After cooling and solidification, the same melt infiltration steps are performed on the opposite side of the infiltration surface. During the infiltration process, factors such as the roughness of the material surface, the wettability between the materials, the insulation temperature and the insulation time will significantly affect the infiltration effect. This technology can prepare composite materials with large plane dimensions and complex surface shapes at low cost, and is suitable for mass production. The present invention successfully combines alloys such as Ag-Cu with porous Ca 3 Co 4 O 9 Ceramic composites were prepared with a honeycomb sandwich structure, and a method for effectively increasing Ca 3 Co 4 O 9 The method of improving the performance of metal-ceramic materials has further broadened its application areas.

[0038] The following is further described in conjunction with specific embodiments.

[0039] Example 1: Preparation process of atmospheric pressure infiltration process Step 1: Pretreatment of ceramic matrix and reinforcement phase.

[0040] Step 1.1 Use the modifier TEOA to prepare a modified solution with a concentration of 1 mol / L.

[0041] Step 1.2: Porous Ca 3 Co 4 O 9 The ceramic wire is cut into small cubes of 2×2×3 cm and placed in a beaker. The solution prepared in 1.1 is drained into the beaker with a glass rod until the Ca 3 Co 4 O 9 The ceramic substrate was immersed, sealed with plastic wrap and immersed for 24 h. 3 Co 4 O 9 The ceramic substrate is taken out and placed in an insulated box for drying and standby use.

[0042] Step 1.3: The roughness of the ceramic surface and the oxide layer of the alloy have a great influence on the infiltration effect. Therefore, it is necessary to test the modified Ca 3 Co 4 O 9 The ceramic matrix and alloy were pretreated accordingly. The porous Ca was sanded in sequence using sandpapers of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh.3 Co 4 O 9 The ceramic was polished until the surface was smooth, and the polished sample was polished with a polishing machine for 15 minutes to ensure that there were no obvious scratches on the surface. After polishing, it was ultrasonically cleaned 3 times in a beaker containing alcohol, and then dried for use. The alloy was polished with sandpaper before the experiment, and then polished to remove the oxide layer on the surface before use.

[0043] Step 2, Ag-Cu alloy / Ca 3 Co 4 O 9 Study on atmospheric pressure infiltration process of cermet Step 2.1, put the polished AgCu28 alloy raw material into the crucible, and add the modified Ca 3 Co 4 O 9 The ceramic substrate is fixed above the alloy and fed into the quartz tube, and the tube furnace is closed; Step 2.2, purge the tube furnace: first connect the pipeline; then, introduce argon into the furnace chamber at a flow rate of 50 ml / min for 10 min until the air in the furnace is basically exhausted; Step 2.3, after purging, the tube furnace was heated to 1173 K at a heating rate of 5 K / min; then the temperature was kept for 2 h; finally, the tube furnace was naturally cooled to room temperature to obtain Ca 3 Co 4 O 9 Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm, which were used to test the pore structure, thermoelectric properties, and mechanical properties.

[0044] Example 2, double-sided vacuum melt infiltration process preparation process Step 1: Pretreatment of ceramic matrix and reinforcement phase.

[0045] Step 1.1 Use the modifier TEOA to prepare a modified solution with a concentration of 1 mol / L.

[0046] Step 1.2: Porous Ca 3 Co 4 O 9 The ceramic wire is cut into small cubes of 2×2×3 cm and placed in a beaker. The solution prepared in 1.1 is drained into the beaker with a glass rod until the Ca 3 Co 4 O 9 The ceramic is immersed, sealed with plastic wrap and immersed for 24 hours. 3 Co 4 O9 Take out the ceramics and put them in an insulated box to dry for later use.

[0047] Step 1.3: The roughness of the ceramic surface and the oxide layer of the alloy have a great influence on the infiltration effect. Therefore, it is necessary to prepare the modified porous Ca 3 Co 4 O 9 Ceramics and alloys were pretreated accordingly. The porous Ca was sanded in sequence using sandpapers of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh. 3 Co 4 O 9 The ceramic was polished until the surface was smooth, and the polished sample was polished with a polishing machine for 15 minutes to ensure that there were no obvious scratches on the surface. After polishing, it was ultrasonically cleaned 3 times in a beaker containing alcohol, and then dried for use. The alloy was polished with sandpaper before the experiment, and then polished to remove the oxide layer on the surface before use.

[0048] Step 2, Ag-Cu alloy / Ca 3 Co 4 O 9 Research on double-sided vacuum melt infiltration process technology of metal ceramics.

[0049] Step 2.1, put the polished AgCu28 alloy raw material into a crucible, and add the porous Ca 3 Co 4 O 9 The ceramic is fixed above the alloy and then the lid of the vacuum heating furnace is closed; Step 2.2, purge the vacuum heating furnace: first, evacuate the air in the vacuum heating furnace to reduce the pressure in the vacuum heating furnace to below 30 Pa; then, introduce argon gas into the vacuum heating furnace until the pressure in the vacuum heating furnace reaches about 0.5 MPa; finally, maintain the pressure for 50 minutes and then evacuate the gas in the vacuum heating furnace again, and repeat the above steps twice; Step 2.3, after purging, argon gas is introduced into the vacuum heating furnace to atmospheric pressure, and the vacuum heating furnace is heated to 1173 K at a heating rate of 5 K / min; then, the argon gas in the vacuum heating furnace is evacuated until the pressure in the vacuum heating furnace is less than 30 Pa, and the temperature is kept for 0.5 h; finally, the vacuum heating furnace is naturally cooled to room temperature to obtain Ca 3 Co 4 O 9 Metal ceramic.

[0050] Step 2.4, fix the opposite side of the infiltrated surface of the metal ceramic infiltrated in step 2.3 above the alloy. Then close the cover of the vacuum heating furnace; repeat steps 2.2 and 2.3 to obtain Ca 3 Co4 O 9 Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm, which were used to test the pore structure, thermoelectric properties, and mechanical properties.

[0051] This embodiment successfully fills the porous Ca with Ag-Cu alloy by double-sided vacuum melt infiltration technology. 3 Co 4 O 9 The internal pores of the ceramic matrix (see Figure 1 and Figure 2 ). In the SEM-EDS line scan, it can be observed that Ag precipitates from the alloy and fills the pores, while Cu is evenly distributed in the ceramic matrix. In this process, Cu reacts with calcium cobalt oxide, so it easily enters the ceramic matrix, causing Cu to precipitate from the alloy, while Ag does not react with Ca 3 Co 4 O 9 The metal reacts with the ceramic matrix to form a honeycomb sandwich structure (see Figure 3 ), which effectively improves the performance of composite materials.

[0052] (2) Ag-Cu alloy / Ca prepared by double-sided vacuum melt infiltration technology 3 Co 4 O 9 In ceramic composites, in addition to the monoclinic Ca 3 Co 4 O 9 In addition to the ceramic phase, Co was also found 3 O 4 , CuO and Ag diffraction peaks (see Figure 4 ). The appearance of CuO is related to Ca 3 Co 4 O 9 The reaction of ceramics generates CuO and Co 3 O 4 Ag exists in the form of a single substance. Figure 3 From the line scan results, it can be inferred that during the infiltration process, Cu reacts to generate CuO and enters the ceramic matrix, while Ag precipitates and fills the pores. This structure enables the material to break through the melting point limit of the Ag-Cu alloy, making it suitable for higher temperature applications.

[0053] (3) The interface contact resistance was measured at the boundary between the infiltrated and non-infiltrated areas at the infiltration front using the room temperature scanning voltage probe method. The results showed that there was an obvious jump in the resistance at the infiltration front. After calculation, the interface resistivity was 10.8KΩ•cm (see Figure 5 ). This result indicates that the infiltration process has a significant effect on the interfacial resistance characteristics, which may be related to the interface structure and charge transfer mechanism between the metal and ceramic matrix.

[0054] (4) Ca prepared by atmospheric pressure infiltration and vacuum-double-sided melt infiltration technology 3 Co 4 O 9 The thermal conductivity of the base metal ceramic material decreases with the increase of the test temperature. This phenomenon is related to the porous Ca 3 Co 4 O 9 Ceramics. At 1073 K, the thermal conductivity of the vacuum-double-sided melt infiltration sample reached 1.545 W / (m·K), and the thermal conductivity of the atmospheric pressure infiltration reached 1.21 W / (m·K). In addition, due to the better effect of vacuum-double-sided melt infiltration, the metal filling is more sufficient, and the higher thermal conductivity of the alloy, the thermal conductivity of the prepared composite material increases. Further infrared thermal analysis of the vacuum-double-sided melt infiltration sample showed that under the condition of heating with a fixed heat source at 1073 K, the temperature difference between the upper and lower ends of the sample was always large within 20 seconds, indicating that the material exhibits good thermal insulation effect in a high temperature environment. In addition, the sample also exhibits an excellent Seebeck coefficient. At the test temperature of 1073 K, the Seebeck coefficient reached 281.36 μV / K, and the electrical conductivity was also increased to 38.48 S / cm. The Seebeck coefficient of the atmospheric pressure infiltration sample is 213.47 μV / K, and the conductivity is 31.41 S / cm. The introduction of the alloy phase does not significantly improve the conductivity of the ceramic matrix, which is attributed to the existence of the interface resistance. After calculation, the power factors are 0.14 mW / (m·K²) and 0.30 mW / (m·K²), respectively. Finally, the vacuum-double-sided melt infiltration sample shows a higher ZT The value reached 0.24, indicating that the material has good application potential in thermoelectric conversion (see Figure 6-Figure 11 ).

[0055] Example 3 Step 1: Pretreatment of ceramic matrix and reinforcement phase.

[0056] Step 1.1 Use the modifier TEOA to prepare a modified solution with a concentration of 1 mol / L.

[0057] Step 1.2: Porous Ca 3 Co 4 O9 The ceramic wire is cut into small cubes of 2×2×3 cm and placed in a beaker. The solution prepared in 1.1 is drained into the beaker with a glass cup until the Ca 3 Co 4 O 9 The ceramic substrate was immersed, sealed with plastic wrap and immersed for 24 h. 3 Co 4 O 9 The ceramic substrate is taken out and placed in an insulated box for drying and standby use.

[0058] Step 1.3: The roughness of the ceramic surface and the oxide layer of the alloy have a great influence on the infiltration effect. Therefore, it is necessary to test the modified Ca 3 Co 4 O 9 The ceramic matrix and alloy were pretreated accordingly. The porous Ca was sanded in sequence using sandpapers of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh. 3 Co 4 O 9 The ceramic was polished until the surface was smooth, and the polished sample was polished with a polishing machine for 15 minutes to ensure that there were no obvious scratches on the surface. After polishing, it was ultrasonically cleaned 3 times in a beaker containing alcohol, and then dried for use. The alloy was polished with sandpaper before the experiment, and then polished to remove the oxide layer on the surface before use.

[0059] Step 2, Ag-Cu alloy / Ca 3 Co 4 O 9 Study on atmospheric pressure infiltration process of cermet Step 2.1, put the polished AgCu28 alloy raw material into the crucible, and add the modified Ca 3 Co 4 O 9 The ceramic substrate is fixed above the alloy and fed into the quartz tube, and the tube furnace is closed; Step 2.2, purge the tube furnace: first connect the pipeline; then, introduce argon into the furnace chamber at a flow rate of 50 ml / min for 5-10 min until the air in the furnace is basically exhausted; Step 2.3, after purging, the tube furnace was heated to 1173 K at a heating rate of 5 K / min; then the temperature was kept for 2 h; finally, the tube furnace was naturally cooled to room temperature to obtain Ca 3 Co 4 O 9Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm for testing the pore structure and thermoelectric properties.

[0060] Step 3, Ag-Cu alloy / Ca 3 Co 4 O 9 Research on double-sided vacuum melt infiltration process technology of metal ceramics.

[0061] Step 3.1, put the polished AgCu28 alloy raw material into the crucible, and add the modified Ca 3 Co 4 O 9 The ceramic substrate is fixed on top of the alloy, and then the cover of the vacuum heating furnace is closed; Step 3.2, purge the vacuum heating furnace: first, evacuate the air in the vacuum heating furnace to reduce the pressure in the vacuum heating furnace to below 30 Pa; then, introduce argon gas into the vacuum heating furnace until the pressure in the vacuum heating furnace reaches about 0.5 MPa; finally, maintain the pressure for 50 minutes and then evacuate the gas in the vacuum heating furnace again, and repeat the above steps twice; Step 3.3, after purging, argon gas is introduced into the vacuum heating furnace to atmospheric pressure, and the vacuum heating furnace is heated to 1173 K at a heating rate of 2-8 K / min; then, the argon gas in the vacuum heating furnace is extracted until the pressure in the vacuum heating furnace is less than 30 Pa, and the temperature is kept for 0.5 h; finally, the vacuum heating furnace is naturally cooled to room temperature to obtain Ca 3 Co 4 O 9 Metal ceramic.

[0062] Step 3.4, fix the opposite side of the infiltrated surface of the metal ceramic infiltrated in step 3.3 above the alloy. Then close the cover of the vacuum heating furnace; repeat steps 3.2 and 3.3 to obtain Ca 3 Co 4 O 9 Metal ceramics. The prepared samples were ground and polished, and then dried after ultrasonic treatment. Wire cutting was used to obtain samples with sizes of 3 mm×4 mm×15 mm and Φ12.7 mm×3 mm for testing the pore structure and thermoelectric properties.

[0063] In other embodiments, relative to Example 2, the modifier can be replaced by SDBS, DA, KH-550 or NaOH.

[0064] In other embodiments, relative to Embodiment 1, the heating temperature during the normal pressure infiltration process can be 1150 K, 1200 K, 1250 K or 1273 K, and the corresponding holding time can be 2 h, 1.5 h, 1 h or 0.5 h.

[0065] In other embodiments, relative to Example 2, in the double-sided vacuum melt infiltration process, the heating temperature of the vacuum melt infiltration process can be 1150 K, 1200 K, 1250 K or 1273 K, and the corresponding insulation time can be 2 h, 1.5 h, 1 h or 0.5 h.

[0066] In other embodiments, the reinforcing metal can be replaced with Ag or Al-Cu alloy.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material, characterized in that: The following steps are involved: Step 1, modifying porous Ca3Co4O9 ceramics with a modifier solution to obtain a modified Ca3Co4O9 ceramic matrix, wherein the pores in the Ca3Co4O9 ceramic matrix are radial pores; Step 2, polishing and grinding the modified Ca3Co4O9 ceramic substrate to obtain a polished porous Ca3Co4O9 ceramic; Step 3, infiltrating the reinforcing metal into the polished Ca3Co4O9 ceramic matrix by a normal pressure melt infiltration method or a double-sided vacuum melt infiltration method to obtain a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material, wherein the nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material comprises a matrix material and a reinforcing phase, wherein the matrix material is a porous Ca3Co4O9 ceramic, and the reinforcing phase is infiltrated into the pores of the Ca3Co4O9 ceramic or attached to the side walls of the pores of the Ca3Co4O9 ceramic; The process of the atmospheric pressure infiltration method is to place the polished porous Ca3Co4O9 ceramic and the reinforcing metal together in a heating furnace, the lower end of the porous Ca3Co4O9 ceramic is in contact with the upper end of the reinforcing metal, the pores of the Ca3Co4O9 ceramic are radially perpendicular to the reinforcing metal, and the heating furnace is heated and insulated after being washed with protective gas to obtain a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material; The process of the double-sided vacuum melting method is as follows: the polished Ca3Co4O9 ceramic matrix and the reinforcing metal are placed together in a vacuum heating furnace, the lower end of the Ca3Co4O9 ceramic matrix is ​​in contact with the upper end of the reinforcing metal, the pores of the Ca3Co4O9 ceramic are radially perpendicular to the reinforcing metal, the vacuum heating furnace is purged and heated and insulated, and then the Ca3Co4O9 ceramic is turned over, and the purging, heating and insulation are repeated to obtain a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material.

2. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 1, the modifier is any one of TEOA, SDBS, DA, KH-550 or NaOH.

3. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 1, the process of modifying the Ca3Co4O9 ceramic matrix by the modifier solution is to immerse the Ca3Co4O9 ceramic in the modifier solution, seal the container, and immerse and modify it for 24 hours.

4. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 2, the polishing and grinding is to polish the Ca3Co4O9 ceramics with sandpaper of 300 mesh, 500 mesh, 800 mesh, 1000 mesh and 2000 mesh in sequence.

5. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 3, the reinforcing metal is Ag-Cu alloy, Ag or Al-Cu alloy.

6. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 3, the process of gas washing by the atmospheric pressure infiltration method is: argon gas is introduced into the furnace chamber at a flow rate of 30-80 mL / min until the air in the furnace is exhausted.

7. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 3, the heating temperature of the atmospheric pressure infiltration method is 1123-1273 K, and the holding time is 0.5-2h.

8. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: In step 3, the gas washing process in the double-sided vacuum melt infiltration method is as follows: evacuate the air in the vacuum heating furnace to reduce the pressure in the vacuum heating furnace to below 30 Pa; then, introduce argon gas into the vacuum heating furnace until the pressure in the vacuum heating furnace increases to 0.5 Mpa; finally, maintain the pressure for 10-60 min and then evacuate the gas in the vacuum heating furnace again, and repeat the above steps 2 to 3 times.

9. The method for preparing a nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material according to claim 1, characterized in that: The heating process of the double-sided vacuum melt infiltration method is as follows: introducing argon gas into the vacuum heating furnace to atmospheric pressure, heating the heating furnace to 1123-1273 K, extracting argon gas to a pressure of less than 30 Pa in the vacuum heating furnace, and keeping the temperature for 0.5-2 h.

10. A nano / micro honeycomb sandwich structure Ca3Co4O9-based metal ceramic material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It includes a matrix material and a reinforcement phase, wherein the matrix material is porous Ca3Co4O9 ceramic, the pores in the Ca3Co4O9 ceramic matrix are radial pores, and the reinforcement phase is metal, which is filled in the Ca3Co4O9 ceramic pores or infiltrated into the ceramic matrix.

Citation Information

Patent Citations

  • Method for preparing three-dimensional continuous network Cr3C2-Cu composites by utilizing infiltration process

    CN104451237A

  • Iron-based ceramic preform with dispersively distributed wear-resistant ceramic particles and manufacturing method of iron-based ceramic preform

    CN114559039A

  • Calcium cobaltate thermoelectric ceramic with directional micro-nano through holes and preparation method of calcium cobaltate thermoelectric ceramic

    CN115710137A

  • Ceramic electric heater, process and material for its manufacture

    RU2205522C1

  • Method for making a ceramic metal composite

    US5735332A